2019
DOI: 10.31219/osf.io/wzcqs
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Perspective-taking is spontaneous but not automatic

Abstract: Data from a range of different experimental paradigms -- in particular (but not only) the dot perspective task -- have been interpreted as evidence that humans automatically track the perspective of other individuals. Results from other studies, however, have cast doubt on this interpretation, and some researchers have suggested that phenomena that seem like perspective-taking might instead be the products of simpler behavioural rules. The issue remains unsettled in significant part because different schools o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…However, this task is not free from replication issues and validity debates. Some of the later studies using the variations of the dot-perspective task either revealed no bias (e.g., Conway et al, 2017) or the biases were subject to alternative explanations by domain-general mechanisms rather than implicit mentalizing (e.g., Santiesteban et al, 2014;Cole et al, 2016;Conway et al, 2017;O'Grady et al, 2017). As an example of the latter, Santiesteban et al (2014) tested participants in two different versions of the dot perspective task: some trials featured an avatar as in previous experiments, and in the other trials, the avatar was replaced by an arrow with similar low-level features such as color, size, and orientation.…”
Section: Introductionmentioning
confidence: 99%
“…However, this task is not free from replication issues and validity debates. Some of the later studies using the variations of the dot-perspective task either revealed no bias (e.g., Conway et al, 2017) or the biases were subject to alternative explanations by domain-general mechanisms rather than implicit mentalizing (e.g., Santiesteban et al, 2014;Cole et al, 2016;Conway et al, 2017;O'Grady et al, 2017). As an example of the latter, Santiesteban et al (2014) tested participants in two different versions of the dot perspective task: some trials featured an avatar as in previous experiments, and in the other trials, the avatar was replaced by an arrow with similar low-level features such as color, size, and orientation.…”
Section: Introductionmentioning
confidence: 99%
“…However, they make distinct contributions to ToM. Perspective-taking is a means through which people can infer others' mental states (i.e., by adopting their point of view, or their visual perspective), and can be activated relatively spontaneously (O'Grady et al, 2020;Samson et al, 2010). Social inferences about other people (e.g., what they think, want, or feel) influence impression formation, and can be executed either while directly observing behavior, or at a later point, from a memory record of this observed behavior or other information (Apperly, 2010).…”
mentioning
confidence: 99%